Neuendorf : Lagerkatalog 1992. - Galerie Neuendorf, Frankfurt am Main (Frankfurt am Main : Galerie Neuendorf AG, 1992)
Artschwager, Richard ; Baselitz, Georg ; Buckley, Stephen ; Copley, William ; Fontana, Lucio ; Golub, Leon ; Graham, Robert ; Hockney, David ; Immendorff, Jörg ; Koberling, Bernd ; Louis, Morris ; Lüpertz, Markus ; Mang, Rainer ; Metzel, Olaf ; Nay, Ernst Wilhelm ; Nigro, Mario ; Noland, Kenneth ; Penck, A.R. ; Pfahler, Georg Karl ; Phillips, Peter ; Picabia, Francis ; Pinelli, Pino ; Ruscha, Ed ; Walther, Franz Erhard
Neuendorf : Lagerkatalog 1992, Galerie Neuendorf AG, Frankfurt am Main, 9. Juni - 31. Juli 1992
boek